ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE PADA WEBSITE KLENGER BURGER MENGGUNAKAN PENDEKATAN USER EXPERIENCE QUESTIONNAIRE (UEQ) - Muhammad Rakha Abyan (2023)
Klenger Burger is a burger restaurant in Indonesia that has been around since 2006. While most burger restaurants have a western taste, restaurants managed by PT. Kinarya Anak Negeri is here to serve burgers with Indonesian flavors so they can be enjoyed by the tongue of the Indonesian people. Website is one of the media used by companies to communicate directly with customers. Consumer experience when visiting a website will form a perception about the company and associate it with the products offered. Not updating the Klenger Burger website for the last 5 years has caused several problems. The problems are that the information on the website is not updated and the user interface is not very attractive, which is detrimental and does not provide a good experience for website visitors. From a short questionnaire filled out by 20 respondents, the results were 55% of respondents disagreed if the Klenger Burger website was easy to understand, 85% of respondents disagreed if the Klenger Burger website made it easy to get the desired information, 75% of respondents disagreed with the information on the website Klenger Burger is according to needs and 85% of respondents do not agree that the Klenger Burger website has an attractive user interface. The characteristics of the respondents who filled out the questionnaire consisted of 70% male and 30% female, 60% of whom live in the Jakarta area and most are 20-30 years old. This study aims to increase the functionality of the Klenger Burger website by using the User Experience Questionnaire (UEQ) approach. After being analyzed using the UEQ method, it is continued with a redesign of the user interface display using the design thinking method and producing a user interface display that is more attractive to visitors. This study resulted in an increase in the 6 UEQ rating scales which previously had a bad score, namely Attractiveness with a value of 1.80 and was in the Good category, Perspicuity with a value of 1.82 and was in the Good category, Efficiency with a value of 1.69 and was in the Good category, Dependability (accuracy) with a value of 1.67 and is in the Good category, Stimulation (stimulation) with a value of 1.74 and is in the Excellent category, and Novelty (novelty) with a value of 1.35 and is in the Good category.